Kemampuan Berpikir Kritis Mahasiswa Pendidikan Matematika Kelompok Atas Dalam Menyelesaikan Soal Struktur Aljabar Ring Materi Ideal Prima dan Ideal Maksimal - Amaliya Syafitri; Aprilla Putri; Mutiara Anjani Siregar; Tamara Winda; Jurani; Yuka Fadhilla; Siti Maysarah (Jurnal LENTERA: Jurnal Studi Pendidikan, 2023)
This study aims to provide an overview of the creative thinking abilities of students with high mathematical abilities so that lecturers can plan a lesson that can develop students' creative thinking in solving problem solving. This research includes the type of qualitative descriptive research. The subjects of the research were three Semester 6 Mathematics Education students at the State Islamic University of North Sumatra Medan who had been selected and had high ability in solving mathematics. Data on high-level mathematical abilities in this study were obtained from exercises that had been done previously in each student's test book and generated data. Based on the results of research and discussion. The creative thinking ability of students in the top group to solve Ring Algebraic Structure questions, namely in the prime ideal material and also the maximum ideal has reached the category of very creative thinking. So it can be concluded that the creative aspects are: flexibility, fluency, and originality. It can be seen that students are at level 4, which is very creative